The protective effect of coadministration of coenzyme Q10 and vitamin E on myopathy induced by simvastatin in rats - Omar Ammar Hashim; Intesar Tarik Numan; Nadia Hameed Mohammed (Toxicology Reports)
The use of Simvastatin has been reported to induced muscle myopathy, with no effective preventive measures. The study objective is to study the protective effect of CoQ10, vitamin E, and their combination to prevent simvastatin-induced skeletal muscle myopathy in rat models and explore possible mechanisms by measuring muscle biomarkers and histopathological changes. All rats (n = 49) received 80 mg/kg/day of simvastatin to induce myopathy for 30 days, the study includes 7 groups (n = 7): negative control, CMC and cotton seed oils vehicles, simvastatin induction, CoQ10, vitamin E and combination of vitamin E and CoQ10 groups; rats in the intervention groups received either 100 mg/kg CoQ10 or 40 mg/kg vitamin E or their combination once daily orally for 30 days. At the end of the experiment, rats were euthanized by cervical dislocation, and blood and the collected tissue samples were collected to measure creatinine kinase (CKM), malondialdehyde (MDA), total antioxidant capacity (TAOC), inducible nitric oxide synthase-2 (iNOS2), and aldolase. In addition, gastrocnemius muscle histopathology was examined. Treatment with CoQ10, vitamin E, or their combination significantly reduced the levels of CKM, aldolase, iNO2, and MDA and increased TAOC compared to the simvastatin induction group. The combination group showed a superior protective effect than either drug alone. Treatment with vitamin E and CoQ10 showed mild vacuolation and cytoplasm with focal splitting and fragmentation of muscle fibers, scattered central nuclei, and eosinophilic cytoplasm. In conclusion, CoQ10 and vitamin E combined showed a superior protective effect against simvastatin-induced myopathy through antioxidant and antiapoptotic pathways.